6•(-9) =
(-4)•½ =
(-10)•1,5 =
(-⅔) • (-⅖) =
(-18):3 =
2,2:(-2) =
0,8•(-5) =
(-9)•(⅔) =
(-3):(⅓) =


zad.4 Korzystając z równosci 392•143=56 056, oblicz
a) (-3,92)•(-14,3) =
b) 0,392 • (-14,3) =
c) (-5605,6) :143 =
d) (-3,92)•1,43 =
e) (-0,143)• (-392) =
f) (-5605,6:(-39,2) =

3

Odpowiedzi

2010-02-21T18:02:23+01:00
6*(-9)= -54
-4*1/2= -2
(-10)•1,5 = -15
(-⅔) • (-⅖) = 4/15
(-18):3 = -6
2,2:(-2) = -1,1
0,8•(-5) = -0,4
(-9)•(⅔) = -6
(-3):(⅓) = -9


a) (-3,92)•(-14,3) = 56,056
b) 0,392 • (-14,3) = 5,6056
c) (-5605,6) :143 = -39,2
d) (-3,92)•1,43 = -5,6056
e) (-0,143)• (-392) = 56,056
f) (-5605,6:(-39,2) = 1430
2010-02-21T18:07:10+01:00
6•(-9) = -54
(-4)•½ = -2
(-10)•1,5 = -15
(-⅔) • (-⅖) = - 4/15
(-18):3 = -6
2,2:(-2) = -1,1
0,8•(-5) = -4
(-9)•(⅔) = -6
(-3):(⅓) = -9

zad.4
a) (-3,92)•(-14,3) = 56,056
b) 0,392 • (-14,3) = -5,6056
c) (-5605,6) :143 = -39,2
d) (-3,92)•1,43 = -5,6056
e) (-0,143)• (-392) = 56,056
f) (-5605,6):(-39,2) = 143

Według mnie, moje odpowiedzi są najbardziej trafne ;)
  • lemo
  • Rozwiązujący
2010-02-21T18:07:16+01:00
6•(-9) =-54
(-4)•½ =-2
(-10)•1,5 =-15
(-⅔) • (-⅖) = -4/15
(-18):3 = -6
2,2:(-2) = -1,1
0,8•(-5) = -4
(-9)•(⅔) = -6
(-3):(⅓) =-9



a) (-3,92)•(-14,3) =56,056
b) 0,392 • (-14,3) = 5,6056
c) (-5605,6) :143 = -39,2
d) (-3,92)•1,43 =-5,6056
e) (-0,143)• (-392) = 56,056
f) (-5605,6:(-39,2) =14,3
Licze na naj